Upgrade Kompetensi Guru PAI Dalam Merespon Pembelajaran Jarak Jauh Dimasa Pandemi Covid-19 - Muhaemin Muhaemin; Ramdanil Mubarok (Al-Fikr: Jurnal Pendidikan Islam, 2020)
How to improve the competence of Islamic religious. The formulation of the research problem is education teachers in responding to distance learning? The purpose of this study is to describe the improvement efforts made by Islamic religious education teachers to improve their competence. Second: to analyze the dynamics of the implementation of teacher competency improvement. Third: to provide positive suggestions and input for Islamic religious education teachers to improve their competence. The method used in this study is a qualitative research method with a literature review approach and books which are the main reference of this research are Munir's Book, Distance Learning Based on Information and Communication Technology, Bandung: Alfabeta. The conclusion is that in an effort to improve the competence of Islamic religious education teachers, they formulate a strategic plan by paying attention to the objectives and utilization of learning resources, then carry out an interactive, inspiring, and fun learning process. Then from these efforts, the Islamic religious education teacher responded by evaluating to be able to provide maximum results, in the distance learning process by increasing competence, designing distance learning devices, designing the implementation of distance learning, so that the evaluation can measure teacher competence. Islamic religious education in response to distance education to improve the quality of learning carried out remotely during the Covid-19 pandemic in the future.